Studying the Role of Social Influence on Adoption of Artificial Intelligence (AI) in Financial Services - Mr. Vaibhav Sinha; Dr. Ajit Kumar (The Bioscan, 2024)
This paper studies the impact of the role of social influence on adoption of artificial intelligence on financial services. The research model used is the modified Unified Theory of Acceptance and Use of Technology (UTAUT) model. Independent variables likely, performance expectancy, effort expectancy and social influence and their effect on adoption of AI in financial services has been researched using questionnaire method. Judgemental sampling technique was used and the data was analysed using two-step structural equation modelling. Results reveal that performance expectancy, effort expectancy and social influence have a positive influence on the adoption of artificial intelligence on financial services. The findings may help the corporate, technology firms, fintech companies to formulate strategies in accordance to use and adoption of artificial intelligence in the financial services industry. The major limitation of the study is that it does not include the effects of other demographic characteristics like gender, income level, literacy rate, living conditions, and these could be further investigated to have a more holistic understanding of the adaptability of artificial intelligence in the field of finance.